2017
DOI: 10.1088/1741-4326/aa8e0c
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modelling of the interaction of hydrogen with interstitial defects and dislocations in BCC tungsten

Abstract: In a fusion tokamak, the plasma of hydrogen isotopes is in contact with tungsten at the surface of a divertor. In the bulk of the material, the hydrogen concentration profile tends towards dynamic equilibrium between the flux of incident ions and their trapping and release from defects, either native or produced by ion and neutron irradiation. The dynamics of hydrogen exchange between the plasma and the material is controlled by pressure, temperature, and also by the energy barriers characterizing hydrogen dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 80 publications
4
45
2
2
Order By: Relevance
“…A reasonable speculation is that an affinity between carbon and hydrogen might lead to the hydrogen trapping. However, a theoretical study showed that the carbon atoms in lattice defects have only a weak influence on the hydrogen trapping (37), and other modeling has successfully predicted the presence of trapped hydrogen at dislocations in a body-centered cubic lattice (38). Therefore, we believe that the observed hydrogen is directly related to the presence of lattice defects, rather than the result of attraction by segregated carbon atoms.…”
mentioning
confidence: 84%
“…A reasonable speculation is that an affinity between carbon and hydrogen might lead to the hydrogen trapping. However, a theoretical study showed that the carbon atoms in lattice defects have only a weak influence on the hydrogen trapping (37), and other modeling has successfully predicted the presence of trapped hydrogen at dislocations in a body-centered cubic lattice (38). Therefore, we believe that the observed hydrogen is directly related to the presence of lattice defects, rather than the result of attraction by segregated carbon atoms.…”
mentioning
confidence: 84%
“…The trap density ( dislocation density × hydrogen atom trapped per unit length lattice number density of tungsten ) is therefore in the order of 1.0 × 10 −6 atomic fraction. The input dislocation detrapping energy lies in the range of atomistic simulations [26,62], 1.28-1.36 eV for an edge dislocation, and 0.92-0.96 eV for a screw dislocation. The vacancy detrapping energy agrees well with atomistic simulations [63][64][65], being 1.65-2 eV up to the second filling level.…”
Section: Spherical Nanoindentationmentioning
confidence: 98%
“…The corresponding results are summarized in table 1 and are consistent with the literature. The dislocation density is inferred from [60,61], as measured by transmission electron microscopy (TEM), to be in the range (1.9 ± 1.4-5.1 ± 1.7) × 10 12 m m −3 for pure tungsten from the same manufacturer which was recrystallized at 2000 K for 0.5 h and at 1873 K for 1 h. At 325 K, the hydrogen atom trapped per unit length of dislocation is calculated to be 1~2 in [62]. The trap density ( dislocation density × hydrogen atom trapped per unit length lattice number density of tungsten ) is therefore in the order of 1.0 × 10 −6 atomic fraction.…”
Section: Spherical Nanoindentationmentioning
confidence: 99%
“…Another study 18 has shown that H and He atoms are strongly bound to an edge dislocation with the interaction energy of − 0.9 and − 3.0 eV, respectively. In the work by De Backer et al 19 , the interaction of H isotopes with SIA clusters and dislocation loops up to 37 SIAs was addressed, where an interaction energy in the range of − 0.3 to − 0.7 eV was derived. Thus, no information on the interaction of C, O, N and He with SIA clusters (dislocation loops) and of O and N to edge dislocations has been published so far.…”
Section: Introductionmentioning
confidence: 99%